Implementation of Canva-Based Vocabulary Flashcards as A Media for Arabic Language Learning at MTS. Darul Ulum Batuputih Sumenep - Fahrurrozi Fahrurrozi; Moch. Wahib Dariyadi; Nurul Murtadho (Alfuad: Jurnal Sosial Keagamaan, 2025)
The teaching of Arabic in madrasas suffers from vocabulary acquisition, especially among students who start learning the language after completing elementary schoolTraditional methods rely on memorization and have no contextualization, thus being unable to inspire students. With technological developments, digital learning media have been developed to further enhance the effectiveness of learning. This research covers the implementation of Canva-based vocabulary flashcards in Arabic teaching and learning activities at MTs. Darul Ulum Batuputih Sumenep, discussing whether or not its application has furthered vocabulary skill improvement in Arabic and mentioning constraints faced in implementation. The case study method adopts a qualitative design, and during data collection, observation, interview, and documentation were carried out, and during data analysis, an interactive analysis model was adapted from Miles and Huberman by looking for applicable patterns and data relationships. Results have shown that the Canva-based vocabulary flashcards significantly enhance the motivation and engagement of the students in understanding, retaining, and applying their vocabulary in speaking and writing. Moreover, teachers find this medium flexible and easy to adapt, despite challenges regarding limited technological access and teachers' digital competencies. Therefore, training and institutional policy support are essential for optimizing its implementation. Further research is recommended to explore the long-term impact of this digital tool on overall Arabic language proficiency.